Girl reporter blows lid off town! - Ellerbee, Linda (New York : Avon Books, 2000)
Casey Smith, an intrepid eleven-year-old journalist, revives her middle school's defunct newspaper and investigates what looks like an environmental pollution cover-up at the local paper mill.
Keywords: Journalism -- Fiction; Newspapers -- Fiction; Schools -- Fiction; Pollution -- Fiction